"Super Hydrocarbon Reformer Trap" for the Complete Oxidation of Toluene Using Iron‐Exchanged β‐Zeolite with a Low Silicon/Aluminum Ratio. Issue 15 (21st June 2016) - Kobatake, Yasuhiro; Momma, Kiyofumi; Elangovan, Shanmugam P.; Itabashi, Keiji; Okubo, Tatsuya; Ogura, Masaru
Abstract: This study examines the effects of the Si/Al ratio and metal cation exchange of a zeolite on the ability to adsorb and reform unburned hydrocarbons (HCs) in emissions from gasoline vehicles. Iron ion‐exchanged β‐zeolites with a low Si/Al ratio not only trap but also oxidize HCs efficiently, which spurred on the development of a "super HC reformer trap". Toluene temperature‐programmed desorption experiments in an O2 ‐containing stream revealed that >90 % of the adsorbed toluene was converted into CO2, and other oxygenates were not observed. This material could be reused and it retained its performance. The strong adsorption of toluene on the zeolites was derived from two synergistic effects: (1) electrostatic interactions between the π orbital of the aromatic ring and the p orbital of the metal cation and (2) interactions between the positively polarized methyl group of toluene and a basic oxygen atom in the zeolite framework. This new material will pave the way for low‐emission, Pt‐free vehicles. Abstract : Is it a bird? Is it a plane? The new concept of a "super hydrocarbon reformer trap" is proposed. We use Fe ion‐exchanged β‐zeolites with a low Si/Al ratio to not only trap unburned hydrocarbons in emission gas from gasoline vehicles but also to oxidize it into CO2 efficiently. Toluene temperature‐programmed desorption experiments revealed that >90 % of the adsorbed toluene was converted into CO2 . This new material will pave the way for low‐emission, Pt‐free vehicles.